2021
DOI: 10.1111/cts.13027
|View full text |Cite
|
Sign up to set email alerts
|

Associations between uncertainties identified by the European Medicines Agency and national decision making on reimbursement by HTA agencies

Abstract: We aimed to determine whether uncertainties identified by the European Medicines Agency (EMA) were associated with negative relative effectiveness assessments (REA) and negative overall reimbursement recommendations by national health technology assessment (HTA) agencies. Therefore, we identified all HTA reports from HAS (France), NICE (England), SMC (Scotland) and ZIN (the Netherlands) for a cohort of innovative medicines that EMA had approved in 2009-2010 (excluding vaccines). Uncertainty regarding pivotal t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 34 publications
0
8
0
Order By: Relevance
“…Added benefit conclusions were categorized into higher, equal, and less therapeutic value which facilitates comparison and is in line with previous studies on this topic (11;15). Similarities between countries in added benefit conclusions were examined by setting one country as the reference through which the conclusions from the other country were compared.…”
Section: Methodsmentioning
confidence: 65%
“…Added benefit conclusions were categorized into higher, equal, and less therapeutic value which facilitates comparison and is in line with previous studies on this topic (11;15). Similarities between countries in added benefit conclusions were examined by setting one country as the reference through which the conclusions from the other country were compared.…”
Section: Methodsmentioning
confidence: 65%
“…This is in line with a study that researched the effect of uncertainty on HTA decisions. 8 In that study, high uncertainty was related a 1.9-fold increased risk of negative relative efficacy assessments and 1.6-fold increased risk of negative overall reimbursement recommendations. That study suggested that, with medium level of uncertainty, clinical and economic restrictions, unmet medical need, and price-related aspects could help HTA bodies consider the uncertainty as acceptable.…”
Section: Discussionmentioning
confidence: 85%
“…With oncology drugs, there is often a high unmet medical need. 8 A non-oncology-specific comparative analysis showed that a high level of full agreement was reached between European Union regulators and participating HTA bodies, through the process of parallel scientific advice. 6 This differs from our analysis, which showed a low level of full alignment between HTA bodies and EMA and a high level of partial alignment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uncertainty management refers to carefully balancing the benefits of reducing uncertainty with the efforts of doing so and the opportunity costs of the alternatives (2). The added value of reducing uncertainty has many dimensions, for example, improved knowledge on treatment efficacy or safety, a reduced possibility for decision errors, a better understanding of the relative effectiveness or associated costs reducing the risk of healthcare displacement or efficiency in the design and implementation of solutions (2;6;1013). The costs associated with uncertainty reduction in terms of additional evidence generation can be tackled to some extent through value of information (VOI) analyses (14).…”
Section: Introductionmentioning
confidence: 99%